ETS2 alleviates acute‐on‐chronic liver failure by suppressing excessive inflammation. Issue 4 (11th April 2023) - He, Lulu; Cai, Qun; Liang, Xi; Xin, Jiaojiao; Shi, Dongyan; Ren, Keke; Li, Yun; Chen, Jiaxian; Sun, Suwan; Guo, Beibei; Yang, Hui; Li, Bingqi; et al.
Abstract: Hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) is a syndrome with high short‐term mortality. The mechanism of the transcription factor ETS2 in ACLF remains unclear. This study aimed to clarify the molecular basis of ETS2 in ACLF pathogenesis. Peripheral blood mononuclear cells from patients with HBV‐ACLF ( n  = 50) were subjected to RNA sequencing. Transcriptome analysis showed that ETS2 expression was significantly higher in ACLF patients than in patients with chronic liver diseases and healthy subjects (all p  < 0.001). Area‐under‐ROC analysis of ETS2 demonstrated high values for the prediction of 28‐/90‐day mortality in ACLF patients (0.908/0.773). Significantly upregulated signatures of the innate immune response (monocytes/neutrophils/inflammation‐related pathways) were observed in ACLF patients with high ETS2 expression. Myeloid‐specific ETS2 deficiency in liver failure mice resulted in deterioration of biofunctions and increased expression of pro‐inflammatory cytokines (IL‐6/IL‐1β/TNF‐α). Knockout of ETS2 in macrophages confirmed the downregulation of IL‐6 and IL‐1β caused by both HMGB1 and lipopolysaccharide, and an NF‐κB inhibitor reversed the suppressive effect of ETS2. ETS2 is a potential prognostic biomarker of ACLF patients that alleviates liver failure by downregulating the HMGB1‐/lipopolysaccharide‐triggered inflammatory response and may serve as a therapeutic target for ACLF.